Factors Affecting the Cervical Cancer Screening Behaviors of Japanese Women in Their 20s and 30s Using a Health Belief Model: A Cross-Sectional Study - Zhengai Cui; Hiromi Kawasaki; Miwako Tsunematsu; Yingai Cui; Masayuki Kakehashi (Current Oncology, 2022)
In recent years, the incidence and mortality rates of cervical cancer (CC) have increased among young women. Cervical cancer screening (CCS) is crucial to reducing the incidence and mortality of CC in a country such as Japan, where it is challenging to raise HPV vaccination rates. The purpose of this study was to identify psychological and personal characteristics relating to CCS participation among young people by using the Health Belief Model (HBM). For this cross-sectional study, an internet survey was conducted between February–March 2018. Based on HBM and personal characteristics, χ2 tests and logistic analyses were used to identify factors influencing CCS. Responses obtained from 816 women in their 20s and 30s were used in the analysis. For HBM-based psychological characteristics, the odds ratios were significantly higher for “cues to participation in screening” and “barriers to participation at the time of cancer screening”, while “barriers to participation before cancer screening” showed significantly lower odds ratios. On the other hand, it was found that the presence of children and having regular health checkups affected the attributes of screening that were significant for decision-making. Therefore, it is important to create proactive measures to encourage younger women to undergo medical examinations.